HALAQAH TRADITION IN BUILDING RABBANI CHARACTERS IN PESANTREN AL-ISLAM LAMONGAN, EAST JAVA, INDONESIA - Muhammad Hambal (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2017)
AbstractThis research aims to reveal the basis of the halaqah practice in the Pesantrenal-Islam Lamongan, the implementation of the learning and formation ofcharacter through halaqah, and the way the system may build Islamic personality.The method used in this reseach was qualitative. The results of this researchare as follows. Firstly, the halaqah practiced in the pesantren al-Islam was basedon the ideas presented by the kyais and the management as formulized inthe khiththah of the pesantren namely to have a rabbani generation with faithand sincerity, good morals, high spirituality, wide knowledge insights, healthyand strong physical condition, and readiness to make some propaganda aboutIslam. Secondly, the implementation of halaqah in Pesantren al-Islam maybe classified into two categories. (1) halaqah taklim, intended to give someinsights to the santries on the right aqidah and the correct worship. Theemployed techniques of the halaqah implementation were bandongan, soroganor the combination of the two. (2) halaqah tarbiyah, intended to build santriesto become muslims with noble morals and with some awareness and spirits ofteaching and of struggling Islam. The technique of the halaqah implementationis to give materials of tazkiyat al-nafs accompanied with ‘amaliah ibadah sunnah,and teaching and harakah materials and also guidance in reciting the HolyQur’an and in guiding the characters. Keywords: Halaqah, Character Building, Pesantren.